THE COMPARISON BETWEEN DEFICIT FUNCTIONAL NEUROLOGIST WITH VON WILLEBRAND FACTOR LEVELS IN ACUTE THROMBOTIC STROKE PATIENTS - Sari, Ita Muharram; Islam, Mohammad Saiful (Malang Neurology Journal, 2016)
Background. There are limited studies of von Willebrand factor (vWF) and thrombotic stroke, escpecially the relationship between level of vWF and functional neurological deficit. Objective. To determine the difference between functional neurological deficit; measured by the NIHSS scale with the vWF level. Methods. Design study was cross sectional, sampling by consecutive admission according to inclusion and exclusion criteria. Blood samples were taken for vWF measurement. Patients are divided into two categories, low vWF level and high vWF levels. Deficit functional neurologist was measured by NIHSS scale.Results. The results were analyzed by chi square. From 80 patients, the result compares the level of NIHSS scale. In grup with mild NIHSS and low vWF levels (50 %) higher than grup with mild NIHSS and high vWF levels (27,27 %). In other side, grup with moderate NIHSS and low vWF levels (50 %) lower than grup with moderate NIHSS and high vWF levels (72,73 %). The difference is not significant statistically (p=0.067).Conclusion. There was no difference between deficit functional neurologist measured by NIHSS scale with von Willebrand factor levels in acute thrombotic stroke patients.